"Self-repairing" nanoshell for cell protection. Issue 1 (29th October 2014) - Jiang, Nan; Yang, Xiao-Yu; Ying, Guo-Liang; Shen, Ling; Liu, Jing; Geng, Wei; Dai, Ling-Jun; Liu, Shao-Yin; Cao, Jian; Tian, Ge; Sun, Tao-Lei; Li, Shi-Pu; et al.
Abstract : Self-repairing biohybrid nanoshells provide living cells with high activity and extended viability in harsh micro-environments. Abstract : Self-repair is nature's way of protecting living organisms. However, most single cells are inherently less capable of self-repairing, which greatly limits their wide applications. Here, we present a self-assembly approach to create a nanoshell around the cell surface using nanoporous biohybrid aggregates. The biohybrid shells present self-repairing behaviour, resulting in high activity and extended viability of the encapsulated cells (eukaryotic and prokaryotic cells) in harsh micro-environments, such as under UV radiation, natural toxin invasion, high-light radiation and abrupt pH-value changes. Furthermore, an interaction mechanism is proposed and studied, which is successful to guide design and synthesis of self-repairing biohybrid shells using different bioactive molecules.